Hubungan antara Self Esteem dengan Online Dating Deception pada Pengguna Aplikasi Kencan di Kota Bandung - Hazrina; Nugraha, Suci (Bandung Conference Series: Psychology Science, 2024)
Abstract. The increasing popularity of online dating apps such as Tinder and Bumble has brought attention to the phenomenon of online dating deception, where a person intentionally misrepresents himself with an identity different from reality in establishing an online relationship in an online dating setting. One possibility for individuals to engage in online deception is due to their self-esteem (Baumeister et al., 1989). This study aims to determine the relationship between self-esteem and online dating deception in dating application users, especially Tinder and Bumble. This research was conducted with a quantitative correlational approach. There were 314 participants in this study aged 18-40 years who actively used the dating applications Tinder and Bumble by filling out online questionnaires via the Google Form. The measuring instrument used in this research is the Coopersmith Self-Esteem Inventory which is based on Coopersmith's theory (1967) and Deception Behavior In Social Media which is based on Utz's theory (2005). The results of this study show a significance value of 0.876 > 0.05, meaning that there is no significant relationship between self-esteem and online deception in users of online dating applications Tinder and Bumble with a correlation coefficient of -0.009. This finding confirms that other factors may be more influential in driving individuals to engage in online deception in the context of online dating. Abstrak. Meningkatnya popularitas aplikasi kencan online seperti Tinder dan Bumble telah membawa perhatian pada fenomena online dating deception, yaitu saat seseorang secara sengaja melakukan representasi diri yang menipu dengan identitas yang berbeda dari kenyataan dalam menjalinkan hubungan online di setting kencan online. Salah satu kemungkinan individu melakukan online deception dikarenakan self-esteem mereka (Baumeister et al., 1989). Penelitian ini bertujuan untuk mengetahui hubungan antara self esteem dan online dating deception pada pengguna aplikasi kencan khususnya Tinder dan Bumble. Penelitian ini dilakukan dengan pendekatan kuantitatif korelasional. Partisipan dalam actorian ini berjumlah 314 orang berusia 18-40 tahun yang aktif menggunakan aplikasi kencan Tinder dan Bumble dengan mengisi kuesioner secara online melalui Google Form. Alat ukur yang digunakan dalam penelitian ini adalah alat ukur Coopersmith Self esteem Inventory yang didasarkan pada teori Coopersmith (1967) dan Deception Behavior In Social Media yang didasarkan pada teori Utz (2005). Hasil actorian ini menunjukkan nilai signifikansi 0.876 > 0.05, artinya tidak terdapat hubungan yang signifikan antara self esteem dengan online deception pada pengguna aplikasi kencan online Tinder dan Bumble dengan nilai koefisien korelasi -0.009. Temuan ini menegaskan bahwa actor-faktor lain mungkin lebih berpengaruh dalam mendorong individu untuk terlibat dalam online deception dalam konteks kencan online.